2006
DOI: 10.1063/1.2177125
|View full text |Cite
|
Sign up to set email alerts
|

Impedance behavior of spin-valve transistor

Abstract: Articles you may be interested inSpin-valve transistors with high magnetocurrent and 40 μA output currentThe magnetoimpedance ͑MZ͒ effect of the pseudo-spin-valve transistor ͑PSVT͒ was investigated at room temperature in the frequency ranged from 100 Hz to 15 MHz. The PSVT can be regarded as a complex combination of resistors, inductors, and capacitors, while the impedance ͑Z͒ consists of a real part, the resistance ͑R͒, and an imaginary part, the reactance ͑X͒. Besides, all these components exhibit magnetic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…At the same time, these phenomena undoubtedly have an application potential. Indeed, the dc and ac magnetoresistive effects can be used in different magnetic sensors [7][8][9][10][11] and can be useful for fabricating, for example, the double-control devices that are sensitive to both magnetic field and optical radiation. In addition, it was demonstrated that simple magnetoresistive elements can be used even in magnetic-field-controlled logic for implementation of Boolean logic functions [12].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, these phenomena undoubtedly have an application potential. Indeed, the dc and ac magnetoresistive effects can be used in different magnetic sensors [7][8][9][10][11] and can be useful for fabricating, for example, the double-control devices that are sensitive to both magnetic field and optical radiation. In addition, it was demonstrated that simple magnetoresistive elements can be used even in magnetic-field-controlled logic for implementation of Boolean logic functions [12].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is an intensive increase in the integration rate of elements of integrated circuits (p-n-junctions, transistors,…) [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. At the same time this has attracted an increasing interest in their performance.…”
Section: Introductionmentioning
confidence: 99%
“…This change leads to decrease in elements integrated circuits [21]. One way to increase performance of elements of integrated circuits is determination of materials with higher values of charge carriers mobility [1][2][3][4][5][6][7][8][9][10][11][12][13][14][22][23][24][25]. Other ways to increase performance are elaboration of new technological processes and modification of existing ones.…”
Section: Introductionmentioning
confidence: 99%
“…One of the actual questions of the solid state electronics is increasing of integration rate of elements of integrated circuits [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. At the same time with decreasing of integration rate of elements of integrated circuits one can find decreasing of dimensions of the elements.…”
Section: Introductionmentioning
confidence: 99%